PENGARUH KEMAMPUAN KERJA TERHADAP KINERJA GURU PEGAWAI NEGERI SIPIL SMP NEGERI 10 PEKANBARU - Dewi, Diana Sri (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
This research was conducted at State Junior High School 10 in Pekanbaru by distributing questionnaires to all civil servant teachers. The purpose of this study is to determine the effect of work ability on the performance of civil servant teachers working at State Junior High School 10 Pekanbaru. A sample of 40 teachers working at the school was chosen for the study.The sample used in this study consisted of 40 people. The study found that the equation Y = 28,486 + 0.391X best describes the relationship between X and Y. Judging from the obtained uji_t results. Judging by the uji_t results obtained That thitung value from 2.072> to 2.02439, through uji_t can be inferred The ability to work has a significant impact on the performance of a civil servant SMP teachers Negeri 10 Pekanbaru, coefficient calculation The determination of (R2) has a value of 0.101.This indicates that its working capacity Significant impact on the performance of civil service teachers by the remaining 10.1% of the 89.9% other variable not included in the study.